A multi-attribute decision model for intrusion response system - Fessi, B. A.; Benabdallah, S.; Boudriga, N.; Hamdi, M. (Elsevier Inc., 2014)
The objective of this paper is to present a multi-attribute decision model for network intrusion response. The proposed technique uses a weighted linear combination (WLC) model to standardize the different attributes to a common numeric range before applying a genetic algorithm to determine the appropriate alternative. The model is characterized by a new implementation of individual structure based on the response-resource matrix and a fitness function based on cost-benefit approach. The decision model parameters are represented by vectors modeling the different attributes that are respectively: financial cost, reputation loss, and processing resources. The paper presents a new approach for handling a multi-attribute decision problem in intrusion response context which has not been addressed in previous studies. Finally, this paper will discuss the findings of simulation experiments and will conclude by discussing the effectiveness of the proposed approach. Â© 2014 Elsevier Inc. All rights reserved.